A Comparison Study on Species Diversity of Woody Plants in Mountain Parks and Riverside Parks of Fuzhou City. Issue 2 (March 2021) - Lan, Yuxiang; Liu, Fan; Lin, Yingfang; Chen, Han; Li, Junyi; Chen, Ye; Dong, Jianwen
Abstract: In order to know the situation of plant diversity of mountain parks and riverside parks in Fuzhou city, the woody plants of different mountain parks and riverside parks in Fuzhou city were studied in this paper. The typical sampling method was used in this survey. Then the composition of plant community, the origination of plants and the species diversity index were analyzed to explore the differences of plant diversity between different types of parks. The research was aimed to provide basic data for the biodiversity conservation in Fuzhou city. The results showed that the species of woody plants of mountain parks and riverside parks was abundant, the similarity of the composition of plant community is extremely high, the number of woody plant species and the application proportion of native tree species of mountain parks was higher than that of riverside parks. The abundance index and the Shannon-Wiener index of tree layer of mountain parks was higher than that of riverside parks. The abundance index and the Shannon-Wiener index of shrub layer of mountain parks was lower than that of riverside parks.